Search
Ask a question
0 0

find (f-g)(-1) when f(x)=5x^2-6 and g(x)= x+4

Algebra is hard and i need help. If you have alot of patience please come help. Need help with functions. This is my fourth math class, and it is tough.

Tutors, please sign in to answer this question.

1 Answer

(f - g)(x) means f(x) - g(x)

(f - g)(x) = 5x2 - 6 - (x + 4)

(f - g)(x) = 5x2 - 6 - x - 4

(f - g)(x) = 5x2 - x - 10


Now we can substitute -1 for x in (f - g)(x)

(f - g)(-1) = 5(-1)2 -(-1) -10

(f - g)(-1) = 5(1) + 1 - 10

(f - g)(-1) = 5 + 1 - 10

(f - g)(-1) = 6 - 10

(f - g)(-1) = -4